Abnormal Nerve Conduction Parameters in Young Diabetic Patients at Diagnosis (BIRDEM Medical Journal, 2016)
Background and Objectives: Diabetes in the young patients, less than 30 years of age, usually has sudden onset and severe hyperglycemia who are resistant to ketosis. Taking the advantage of this uniqueness of this group of patients the present study was aimed to evaluate their peripheral nerve functional status, explore its relationship with glycemic status and find out utility of nerve conduction study for detection of neuropathy at diagnosis to introduce timely intervention in the necessary cases.Materials and Methods: A total number of 32 newly diagnosed untreated diabetic patients, age 30 years or less, consecutively attending the BIRDEM Out-patient department were recruited. Age-matched healthy subjects (n=30) with no family history of diabetes served as controls. Motor and sensory conduction velocities (NCV), distal latencies (DL), compound muscle and sensory nerve action potentials (CAMP, SNAP) of ulnar, peroneal and sural nerves were studied following standard protocol. Glucose was determined by glucose-oxidase, Fructosamine by enzymatic colorimetric method.Results: Ulnar motor NCV (m/sec, mean±SD) was significantly slower in diabetic group compared to the controls [58.29±6.88 vs 66.56±6.13; p